Risk Aversion and Budget Uncertainty: Empirical Evidence on Year-End Government Spending Spikes in Indonesia - Yalisman, Febrian; Khoirunurrofik, Khoirunurrofik (Indonesian Treasury Review: Jurnal Perbendaharaan, Keuangan Negara dan Kebijakan Publik, 2025)
Research Originality — Existing empirical research on year-end government spending spikes seldom employs well-defined indicators of risk aversion behavior. Moreover, most analyses rely on limited samples or macro-level data, posing difficulties regarding generalizability. This study contributes originality by examining behavioral responses at the micro-level of individual work units (Satkers) across all ministries and agencies (MAs) in Indonesia. It further offers novelty by employing external budget revision data as a proxy for risk aversion behavior related to year-end government spending spikes. Research Objectives — This study aims to identify and quantify the impact of risk aversion behavior, driven by budget uncertainty, on year-end spending spikes among Satkers in Indonesia's ministries and agencies. The analysis focuses specifically on the accumulation of goods and capital expenditures, which constitute the primary components of year-end spending spikes. Research Methods — This study used quarterly budget revision and expenditure data from 13,080 Satkers across all MAs for the periods 2018–2022. A quasi-experimental approach using the instrumental variable-two-stage least squares (IV-2SLS) method was employed to mitigate potential biases caused by reverse causality and omitted variable bias. Empirical Results — The findings indicate a behavioral tendency toward risk aversion in response to budget uncertainty, which leads to year-end spending spikes. Empirical estimates showed that each additional external budget revision was associated with increased budget absorption by 1.697 percentage points, ceteris paribus. Furthermore, the manifestation of risk aversion behavior varied across islands and government sectors. Implications — To anticipate and mitigate spending spikes, the Ministry of Finance is encouraged to develop a data-driven monitoring system to track and predict Satker spending behavior. In addition, both the Ministry of Finance and the technical ministries should enhance their guidance and capacity-building efforts for Satker financial management personnel.